Opções de mitigação das emissões de gases de efeito estufa na indústria de petróleo e gás natural brasileira - Hargreaves, Fernanda Martins (2019)
The oil and natural gas industry is responsible for the emission of greenhouse gases (GHG) that occurs from the burning of fossil fuels and emissions from fugitive sources. Currently, stakeholders urge in order to reduce these emissions, however, there is a trend of increasing activity and emissions both in the world and in Brazil. This study analyzed the mitigation options for GHG emissions from the Upstream and Downstream, based on actions already taken by companies, regulations and best technological practices implemented in different countries. For this, four scenarios were constructed, one characterizes a trend, representing emission reductions from actions already taken by the industry, and three including proposed mitigation options. As a result, are observed the greatest GHG emission reduction potentials are related to Upstream and to the Carbon Capture and Storage (CCS) application scenario.